Soka River Flood Modelling Using HEC – RAS (Case Study of Kedungsana Village) - Gusti Suryana Putra; Vier Andrean; Putri Karina Febiani; Sulistijo Edhy Purnomo (Riviera Publishing, 2026)
Cirebon Regency is experiencing rapid development, which has led to significant changes in land use. Improperly managed land-use changes have resulted in a reduction of water catchment areas, decreasing the soil’s capacity to absorb rainfall and increasing the potential for flooding. Along with the expansion of residential areas and the growing intensity of human activities, river management problems—such as flooding and erosion—have become more frequent. Therefore, an effective river management system is needed to minimize these negative impacts. The purpose of this study is to evaluate the flood potential of the Soka River in Kedungsana Village, Cirebon Regency, using HEC-RAS hydraulic modeling. This analysis was conducted using annual maximum rainfall data from several rain stations, discharge calculations, and flood plan simulations based on the Nakayasu method and HEC-RAS modeling. The results show that parts of the Soka River’s cross-section are unable to accommodate flow discharge during the planned flood recurrence period, which may lead to overflow. It is hoped that this research will serve as the basis for recommendations to mitigate flooding in the study area.